Enhancing Operational Performance in the Manufacturing Sector: A Review on the Role of Supply Chain Digitization and Visibility - Khan, Tahsina; Habib, Md. Mamun (International Journal of Supply Chain Management, 2025)
The objective of this research is to comprehensively assess the impact of digitization and enhanced visibility in supply chain performance improvement of the manufacturing industry. The methodological approach adopted was systematic in examining contemporary empirical research and frameworks focused on supply chain digitization and visibility. The research shows that various indicators of performance are significantly improved by combining processes such as supply chain digitization with better visibility, including reduced lead times, more effective inventory management, and increased responsiveness in supply chain. Although many of these breakthroughs have been accomplished, there are still numerous practical challenges, like harmonizing data systems, protecting data, and dealing with resistance from the users. The study will be of value to the practitioners because it emphasizes the pivotal role played by blending the use of digital solutions with visibility practices in simplifying supply chain processes. The study suggests that the digital strategies to supply chain management could lead to greater resilience and adaptability, and as such, enhance better efficiency in supply chain management. This analysis provides a new insight into the combination of digitization and visibility in supply chains, a unified picture of the combined contributions to operational success.